Informal settlements: Campos acadêmicos e geopolítica - Renato Nunes Balbim; Cristine Diniz Santiago (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This is the fourth and last in a series of four discussion papers (DP) that are part of the research How Cities are Divided: the invention of informal settlements. The goal of this series of DPs was to carry out a culturomic and scientometric study on the use of the term informal settlements contextualized by previous geopolitical and public policies analysis. Final remarks are presented seeking not only to summarize the findings of this research, but also to relate them objectively to other previous findings that involved the analysis of policies, programs, agendas, guidelines and proposals from international agencies and governments. In general, this paper presents the trajectory of the term informal settlements based on the research of greater scope about the available related academic production. Thus, it was possible to demonstrate empirically how the theoretical bases used reveal how science, intentionally or not, contributes to the maintenance of the hegemonic geopolitical model of center-periphery based on dependence, even regarding the formulations and ideas, moving away from models that value interdependence and uncritically reproducing terms such as informal settlements.
10419/284892
Keywords: R28; H76; O18; 330; informal settlements; urban management; bibliometric analysis; UN-Habitat; slum